Inside the academy and out: lesbian/gay/queer studies and social action - Ristock, Janice L.; Taylor, Catherine G. (University of Toronto Press, 1998)
Inside the Academy and Out demonstrates that the pedagogical and theoretical insights offered by lesbian/gay/queer studies can have relevance to a broader social sphere. The essayists represented here come from a wide range of disciplines, including English, education, philosophy, sociology, and women's studies. Their essays are divided into two broad areas: 'Pedagogy and Research' and 'Spheres of Action.' Taken together, they explore teaching and research theory, examining their implications in areas such as AIDS education, social services, law reform, and popular culture.
Section: xi, 365 pages ; 24 cm
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; droit; ethnographie; intersectionnalité; justice sociale; militance; premier cycle; pédagogie; périodes historiques; queer; santé; science politique et droit; sciences de l'éducation; sciences humaines; sexologie; soc2014; thématiques; violences

Démocratie et représentation - Riot-Sarcey, Michèle (Kimé, 1995)
La représentation politique est aujourd’hui en crise : partout en Europe, la légitimité des représentants est contestée, sans pour autant que la démocratie, en son principe, soit mise en cause. A partir de ce constat, des chercheurs des différentes disciplines ont questionné la représentation dans son actualité politique et dans sa formation historique. L’usage de la représentation, la délégation d’autorité qu’elle suppose, la violence qu’elle engendre, la domination qu’elle implique, la pratique démocratique qu’elle présuppose ont été soumis à examen par les intervenants au colloque organisé par le Centre Culturel de l’Albigeois. Les disfonctionnements et les apories d’une démocratie, longtemps considérés comme une donnée perfectible, se révèlent comme un simple produit des règles d’un système exclusif, qui contribuent largement à tenir à l’écart des pouvoirs et des lieux de représentation politiques les femmes comme la grande majorité d’une population, par ailleurs de plus en plus politisée.
Keywords: 1900-1999; 1990-1999; approches et analyses; cours; discipline; fem1000; interdisciplinarité; occident; premier cycle; périodes historiques; représentation politique; science politique; science politique et droit; sciences humaines; théories féministes

Only words - MacKinnon, Catharine A. (Harvard University Press, 1993)
When is rape not a crime? When it's pornography–or so First Amendment law seems to say: in film, a rape becomes "free speech." Pornography, Catharine MacKinnon contends, is neither speech nor free. Pornography, racial and sexual harassment, and hate speech are acts of intimidation, subordination, terrorism, and discrimination, and should be legally treated as such. Only Words is a powerful indictment of a legal system at odds with itself, its First Amendment promoting the very inequalities its Fourteenth Amendment is supposed to end. In the bold and compelling style that has made her one of our most provocative legal critics, MacKinnon depicts a society caught in a vicious hypocrisy. Words that offer bribes or fix prices or segregate facilities are treated by law as acts, but words and pictures that victimize and target on the basis of race and sex are not. Pornography–an act of sexual domination reproduced in the viewing–is protected by law in the name of "the free and open exchange of ideas." But the proper concern of law, MacKinnon says, is not what speech says, but what it does. What the "speech" of pornography and of racial and sexual harassment and hate propaganda does is promote and enact the power of one social group over another. Cutting with surgical deftness through cases of harassment in the workplace and on college campuses, through First Amendment cases involving Nazis, Klansmen, and pornographers, MacKinnon shows that as long as discriminatory practices are protected as free speech, equality will be only a word.
Section: 152 p. ; 19 cm
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; discipline; droit; histoire et politique; patriarcat; premier cycle; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sciences sociales; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques; violences; états-unis; études de genres